Ubiquitylation within signaling pathways in- and outside of inflammation - Hochrainer, Karin; Lipp, Joachim (Thrombosis and Haemostasis, 2007)
Ubiquitin is a highly conserved 76-amino-acid peptide that becomes covalently attached to lysine residues of target proteins. Since ubiquitin itself contains seven lysine residues, ubiquitin molecules can generate different types of polyubiquitin chains. Lys48-linked polyubiquitylation is well-known as posttrans-lational tag for targeting proteins for degradation by the 26S proteasome. Recent studies have revealed several new functions of ubiquitin, e.g. activation of protein kinases, control of gene transcription, DNA repair and replication, intracellular trafficking and virus budding. These functions are mainly mediated by Lys63 polyubiquitin chains or attachment of a single ubiquitin molecule to one or several lysine residues within the target protein. Importantly, protein ubiquitylation exhibits inducibility, reversibilty and recognition by specialized ubiquitin-binding domains, features similar to protein phosphorylation. In this review we comprehensively describe regulations of protein ubiquitylation and their impact on distinct signaling pathways.
Keywords: Endothelial cells; signal transduction; inflammation